2013
DOI: 10.1177/0017896913510512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a health education programme about traumatic brain injury

Abstract: Objective: Our aim was to evaluate a health education programme (TBI options: Promoting Knowledge) designed to increase public awareness and understanding about traumatic brain injury (TBI) through in-person (classroom) and computer-based (electronic) learning environments. Design: We used a pre-post survey design with randomization of participants to classroom ( N = 22) or electronic ( N = 22) delivery of the programme, in classroom and computer laboratory settings on the campus of Kansas State University, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Both modes appeared equally effective in terms of self-report of change in long-term TBI knowledge outcomes. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Both modes appeared equally effective in terms of self-report of change in long-term TBI knowledge outcomes. 39 …”
Section: Discussionmentioning
confidence: 99%
“…In the study, they found that participants had significantly higher ratings of knowledge after the program experience. [15] The fourth objective was to correlate the pre-test and post-test knowledge and attitude regarding the prevention of head injury among young adults Table 7 shows that the mean score of pre-test knowledge and pre-test attitude on prevention of road traffic accident among young adults was 11.12 and 30.18 with SD of 2.35 and 5.82. "r" value (0.29) showed that there was a positive relationship between knowledge and attitude.…”
Section: The Second Objective Was To Find Out the Attitude Regarding mentioning
confidence: 99%